Composite cathode material with sandwich-like structure, field emission cathode and preparation method and application of field emission cathode

By forming a metal bonding layer between the cathode material layers of carbon nanotubes and other materials, the problem of poor field emission stability of carbon nanotube cold cathode is solved, the field emission life is extended and the stability is improved, and it is suitable for high-end cold cathode products. development.

CN119314842APending Publication Date: 2025-01-14THE GBA NAT INST FOR NANOTECHNOLOGY INNOVATION
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310858186.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-12
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

When existing carbon nanotubes are used as cold cathode electron sources, they are prone to fall off due to the electric field force during field emission, resulting in unstable field emission current and short life, which limits the development and application of high-end cold cathode products.

Method used

Using a composite cathode material with a sandwich-like structure, a metal bonding layer is set between the cathode material layers and a welded structure is formed by melting metal particles to improve the stability of the composite cathode material, and the angle of the emission tip can be adjusted according to different application scenarios. Reduce voltage and extend field emission life.

Benefits of technology

The field emission life and stability of the composite cathode material are improved, the electronic material damage rate caused by ignition is reduced, the selectivity of the cathode material is enriched, and the better field emission performance is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119314842A_ABST
    Figure CN119314842A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of discharge tubes or discharge lamps, and particularly relates to a composite cathode material with a sandwich-like structure, a field emission cathode and a preparation method and application of the field emission cathode. The composite cathode material with the sandwich-like structure comprises a cathode material layer I, a first metal bonding layer and a cathode material layer II which are sequentially stacked, and the cathode material layer I and the cathode material layer II are layers made of at least one material selected from graphene, carbon nanotubes, carbon cloth and ZnO nanowires. And the first metal bonding layer is formed by melting and curing metal particles. According to the composite cathode material, the cathode material layers are welded together to form a stable composite structure by using the metal bonding layer formed by curing the molten metal particles between the cathode material layers, so that the damage rate of an emissive electron material caused by sparking in the field emission process is reduced, and the field emission life of the composite cathode material is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of discharge tubes or discharge lamps, and more specifically, to a composite cathode material with a sandwich structure, a field emission cathode, and a preparation method and application thereof. Background Art

[0002] Graphene or carbon nanotubes are widely used in the electronics field due to their excellent electrical conductivity, good physical and chemical stability, and integrated preparation. In particular, compared with graphene, carbon nanotubes, as electron source materials, have a unique geometric structure with nanometer-scale tips and micrometer-scale or even millimeter-scale lengths, which can provide a high aspect ratio, which is conducive to the local field enhancement of the electric field at the tip, so that the electrons inside the carbon nanotubes can escape into the vacuum under a lower electric field, reducing the applied voltage and energy consumption. A single carbon nanotube can theoretically reach 10 7 A / cm 2 The field emission current density is very high. In actual testing, carbon nanotubes can achieve current emission in the milliampere or even ampere range, which shows great application prospects in cold cathode electron sources.

[0003] However, at present, when carbon nanotubes are used as cold cathode electron sources, they are easily separated from the substrate during the field emission process due to the large electric field force; the emission current density at the local site is too large, resulting in sparks and damage to the carbon nanotubes, which leads to problems such as unstable field emission current and short life, and has many adverse effects on the back-end electron beam control, seriously limiting the development and application of high-end cold cathode products.

[0004] In order to solve the field emission stability problem of carbon nanotube cathode materials, the prior art discloses a method for preparing a composite cathode material with a graphene / zinc oxide / graphene sandwich structure for field emission, wherein a layer of ZnO film is first sputtered on the graphene surface by magnetron sputtering, and the film is used as a seed material, while zinc salt and hexamethylenetetramine are used as raw materials to hydrothermally grow a ZnO nanoneedle array, and then an electrostatic spray deposition technology is used to deposit a graphene film on the surface of the ZnO nanoneedle array, and the ZnO nanoneedle array is used to reduce the start-up strength of the composite cathode material while improving its emission intensity. However, the field emission current stability of the composite cathode material is poor, resulting in a short field emission lifetime. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem of poor field emission current stability of existing field emission composite cathode materials and to provide a composite cathode material with a sandwich-like structure.

[0006] Another object of the present invention is to provide a method for preparing a sandwich-structured composite cathode material.

[0007] Another object of the present invention is to use the above-mentioned sandwich-structured composite cathode material in a cold cathode electron source.

[0008] Another object of the present invention is to provide a field emission cathode comprising the above-mentioned sandwich-like composite cathode material.

[0009] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0010] The present invention protects a sandwich-like composite cathode material, which comprises a cathode material layer I, a first metal bonding layer and a cathode material layer II stacked in sequence;

[0011] The cathode material layer I and the cathode material layer II are both layers comprising at least one material selected from graphene, carbon nanotubes, carbon cloth and ZnO nanowires;

[0012] The first metal bonding layer is formed by melting and solidifying metal particles.

[0013] The present invention forms a sandwich-like structure by arranging a metal bonding layer between cathode material layers, and utilizes the wetting effect of metal particles after melting to infiltrate the surface layer of the cathode material layer adjacent thereto, so that the metal melt forms a welding structure on the surface layer after cooling, thereby improving the stability of the composite cathode material. The metal particles may be metal micron particles or metal nanoparticles; preferably metal nanoparticles, which can be melted better to form a metal bonding layer.

[0014] Preferably, the cathode material layer I and the cathode material layer II are any one of graphene, carbon nanotubes and carbon cloth. Compared with ZnO nanowires, graphene, carbon nanotubes or carbon cloth have better flexibility and are easier to form a support film. After being combined with the metal adhesive layer, the composite cathode material can have higher stability.

[0015] Specifically, the thickness of the cathode material layer I is 3-7 μm, and the thickness of the cathode material layer II is 3-7 μm.

[0016] The thickness of cathode material layer I and cathode material layer II may be the same or different; optionally, the thickness of cathode material layer I is 5 μm, and the thickness of cathode material layer II is 5 μm.

[0017] Preferably, the composite cathode material layer further comprises a second metal bonding layer, the second metal bonding layer comprises a plurality of stacked units, the stacked units comprise a metal layer and a thin film layer stacked;

[0018] The second metal bonding layer is located between the cathode material layer I and the first metal bonding layer, and / or the second metal bonding layer is located between the cathode material layer II and the first metal bonding layer, and the thin film layer is arranged close to the first metal bonding layer;

[0019] The thin film layer is a layer comprising at least one material selected from graphene, carbon nanotubes, carbon cloth, ZnO nanowires, Ag nanowires and Cu nanowires;

[0020] The metal layer is formed by melting and solidifying metal particles, wherein the metal particles may be metal nanoparticles, and the thickness of the film layer is 3 to 7 μm, specifically 5 μm.

[0021] Optionally, the thin film layer is Ag nanowire or Cu nanowire, and is made of a different metal material from the first metal adhesive layer and the metal layer.

[0022] Specifically, the metal particles are any one of Ni particles, Cu particles, Au particles and Ag particles. The shape and particle size of the metal particles are not particularly limited and can be selected according to actual conditions, and can be metal micron particles or metal nanoparticles.

[0023] The present invention also protects a method for preparing a sandwich-like composite cathode material, comprising the following steps:

[0024] Placing the metal particle layer I between the cathode material layer I and the cathode material layer II, heating to melt the metal particles, and cooling to solidify, thereby obtaining a composite cathode material with a sandwich structure;

[0025] The cathode material layer I and the cathode material layer II are both layers of at least one material selected from graphene, carbon nanotubes, carbon cloth and ZnO nanowires.

[0026] Specifically, a cathode material layer I can be first formed by filtration, and then a metal particle layer I is formed by filtration on the cathode material layer I, and a cathode material layer II is formed by filtration on the metal particle layer; the three-layer composite material is then placed in a heating device for high-temperature treatment so that the metal particle layer I melts at high temperature, and then the molten metal particles are solidified by cooling to form a first metal bonding layer, thereby forming a composite cathode material with a sandwich structure.

[0027] The temperature of the high temperature treatment can be selected according to the material of the metal particles, as long as it can melt them. Generally, the cathode material or metal particles are first prepared into a uniform dispersion of a certain solubility, and then filtered to form a multi-layer composite structure. The multi-layer composite structure can also be formed by other methods.

[0028] A plurality of stacked units are further arranged between the metal particle layer I and the cathode material layer I, or between the metal particle layer I and the cathode material layer II. The stacked units include a stacked metal particle layer II and a thin film layer, and the thin film layer is arranged close to the metal particle layer I.

[0029] The thin film layer is a layer including at least any one material of graphene, carbon nanotube, carbon cloth, ZnO nanowire, Ag nanowire and Cu nanowire.

[0030] Specifically, the metal particles in the metal particle layer I and the metal particle layer II are metal nanoparticles and have a particle size of 50 to 100 nm.

[0031] The application of a sandwich-structured composite cathode material in a cold cathode electron source is also within the protection scope of the present invention.

[0032] The present invention also protects a field emission cathode comprising the composite cathode material having a sandwich-like structure.

[0033] Specifically, the field emission cathode has an emission tip, and in different application scenarios, the angle θ of the emission tip can be adjusted according to actual needs (e.g. Figure 1 g) can be adjusted, for example, it can be 40°~55°. A small angle θ can provide a larger field enhancement factor, produce a local field enhancement effect at the tip, and reduce the applied voltage. That is, the angle θ of the emission tip of the field emission cathode can be adjusted to reduce the field shielding effect and reduce the applied voltage, thereby extending the field emission life of the cathode.

[0034] The present invention has the following beneficial effects:

[0035] The sandwich-like composite cathode material of the present invention utilizes a metal bonding layer formed by solidification between cathode material layers after metal particles are melted to weld cathode material layers together to form a stable composite structure, thereby reducing the damage rate of the electron-emitting material caused by ignition during the field emission process to improve the field emission life of the composite cathode material. Moreover, the cathode material layer and the metal bonding layer can realize a structural combination of different cathode materials by constructing different metal bonding layers and different cathode material layers, greatly enriching the selectivity of cathode materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Schematic diagram of the preparation process of the sandwich-structured composite cathode material in Example 1.

[0037] Figure 2 2a is a schematic structural diagram of a sandwich-like composite cathode material of the present invention, wherein 2a is the diameter of the composite cathode material, and 2b is the thickness of the composite cathode material.

[0038] Figure 3 This is a schematic structural diagram of a field emission cathode with an angle θ on the top obtained by cutting the sandwich-like composite cathode material of the present invention, 3a is the thickness of the cathode material layer II, 3b is the thickness of the second metal bonding layer, 3c is the thickness of the core layer, 3d is the thickness of the first metal bonding layer, and 3e is the thickness of the cathode material layer I.

[0039] Figure 4 This is a SEM image of a field emission cathode with a top angle θ of 55°, which is made using the sandwich-structured composite cathode material in Example 1.

[0040] Figure 5 This is a SEM image of a field emission cathode with a top angle θ of 40° made from the sandwich-like composite cathode material in Example 1.

[0041] Figure 6 This is a SEM image of the cross section of the sandwich-structured composite cathode material in Example 1.

[0042] Figure 7 and Figure 8 The curves showing the change of field emission current over time of different field emission cathodes made by using the sandwich-structured composite cathode material in Example 1 are shown.

[0043] Fig. 9 This is an SEM image of the cross section of the sandwich-structured composite cathode material in Example 2. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with the accompanying drawings and specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0045] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.

[0046] Example 1

[0047] A sandwich-structured composite cathode material is prepared by the following preparation method (eg Figure 1 shown):

[0048] S1. Using an organic filter membrane with a diameter of 50 mm and soluble in acetone as a substrate, take an appropriate amount of carbon nanotube dispersion and evenly drop it on the substrate. After vacuum filtration, evenly distributed carbon nanotubes are left on the substrate. Repeat this process several times until the carbon nanotubes are completely and evenly dispersed on the substrate and form a certain thickness (about 5 μm), thus obtaining a carbon nanotube layer 1a ( Figure 1 h film A);

[0049] S2. Take an appropriate amount of Ag nanoparticle dispersion and drop it evenly on the film 1a described in S1. After vacuum filtration, an Ag nanoparticle layer with a thickness of about 5 μm is formed on the film 1a to obtain a film 1b;

[0050] S3. Take an appropriate amount of the carbon nanotube dispersion and drop it evenly on the film 1b described in S2. After vacuum filtration, a carbon nanotube layer with a thickness of about 5 μm is formed on the film 1b ( Figure 1 h film B), to obtain film 1c;

[0051] S4. Take an appropriate amount of Ag nanoparticle dispersion and drop it evenly on the film 1c in S3. After vacuum filtration, an Ag nanoparticle layer with a thickness of about 5 μm is formed on the film 1c to obtain a film 1d.

[0052] S5. Take an appropriate amount of the carbon nanotube dispersion and drop it evenly on the film 1d described in S4. After vacuum filtration, a carbon nanotube layer with a thickness of about 5 μm is formed on the film 1d ( Figure 1 h film C), to obtain film 1e;

[0053] S6. The film 1e is placed in a tube furnace and annealed under Ar gas protection at a temperature of 900°C for 30 min, so that the Ag nanoparticle layer is melted and cooled to form a metal bonding layer, thereby obtaining a sandwich-like composite cathode material (such as Figure 2 shown).

[0054] Among them, the above-mentioned carbon nanotube dispersion can be prepared by the following preparation method: weigh an appropriate amount of carbon nanotubes with a diameter of about 7nm and disperse them in a 0.1wt% sodium dodecyl sulfate solution, and perform ultrasonic treatment in a 60°C water bath for 24 hours to evenly disperse the carbon nanotubes and reduce the agglomeration of the carbon nanotubes, so as to obtain a uniformly dispersed carbon nanotube dispersion with a concentration of 0.5mg / mL.

[0055] Preparation of the above-mentioned Ag nanoparticle dispersion: weigh an appropriate amount of Ag nanoparticles with a diameter of about 50 to 100 nm, disperse them in deionized water, and perform ultrasonic treatment in a 60°C water bath for 24 hours to obtain a uniformly distributed Ag nanoparticle dispersion with a concentration of 0.1 mg / mL.

[0056] Example 2

[0057] A composite cathode material with a sandwich structure is prepared by a method substantially the same as that of Example 1, except that the carbon nanotube dispersion in step S3 is replaced by a graphene dispersion.

[0058] The graphene dispersion can be prepared by the following method:

[0059] An appropriate amount of graphene was weighed and dispersed in a 0.1 wt % sodium dodecyl sulfate solution, and ultrasonic treatment was performed in a 60° C. water bath for 24 h to uniformly disperse the graphene, thereby obtaining a graphene dispersion with a concentration of 0.5 mg / mL and uniform dispersion.

[0060] Example 3

[0061] A composite cathode material with a sandwich structure is prepared by a method substantially the same as that of Example 1, except that the carbon nanotube dispersion in step S3 is replaced by a ZnO nanowire dispersion.

[0062] The ZnO nanowire dispersion can be prepared by the following method:

[0063] An appropriate amount of ZnO nanowires was weighed and dispersed in deionized water, and ultrasonic treatment was performed in a water bath at 60° C. for 24 h to obtain a uniformly distributed ZnO nanowire dispersion with a concentration of 0.1 mg / mL.

[0064] Example 4

[0065] A composite cathode material with a sandwich structure is prepared by a method substantially the same as that of Example 1, except that the thickness of the film A in step S1 and the thickness of the film C in step S5 are both 3 μm, and the thickness of the film B in step S3 is 7 μm.

[0066] Example 5

[0067] A composite cathode material with a sandwich structure is prepared by a method substantially the same as that in Example 1, except that the thickness of the film A in step S1 and the thickness of the film C in step S5 are both 7 μm, and the thickness of the film B in step S3 is 3 μm.

[0068] Example 6

[0069] A composite cathode material with a sandwich structure is prepared by a method substantially the same as that of Example 1, except that the Ag nanoparticle dispersion in step S2 and step S4 is replaced by an Au nanoparticle dispersion.

[0070] Example 7

[0071] A composite cathode material with a sandwich structure is prepared by a method substantially the same as that of Example 1, except that the Ag nanoparticle dispersion in step S2 and step S4 is replaced by a Cu nanoparticle dispersion.

[0072] Performance Testing

[0073] (1) SEM characterization

[0074] Figure 6is a SEM image of a cross section of a sandwich-like composite cathode material in Example 1. Figure 6 It can be seen that the composite cathode material has a five-layer structure (CNT / Ag / CNT / Ag / CNT). After melting, the Ag nanoparticles penetrate into the surface layers of the two adjacent carbon nanotube layers, and form a metal bonding layer after cooling. Different carbon nanotube layers can be welded together, thereby improving the overall stability of the sandwich-like composite cathode material. Fig. 9 This is a SEM image of the cross section of the sandwich structure composite cathode material of Example 2. Fig. 9 It can be found that the composite cathode material has a five-layer structure (CNT / Ag / Graphene / Ag / CNT) similar to the composite cathode material in Example 1, but there are graphene layers between its metal bonding layers. Compared with carbon nanotubes, the local field at the top of the graphene is enhanced, which is more conducive to improving the field emission stability and thus better improving its field emission lifetime.

[0075] (2) Field emission stability test

[0076] The sandwich-like composite cathode materials in Examples 1 to 7 are cut by laser to obtain cathodes with a specific angle θ (such as Figure 3 Specifically, the laser frequency is 1000 Hz, the pulse width is 120 fs, the wavelength is 800 nm, the laser energy is about 0.3 W, the spot diameter is less than 10 μm, and the cutting speed is 0.2 ms / s.

[0077] The cathodes at different angles in Example 1 were tested for field emission stability. The test results are as follows: Figure 7 and Figure 8 As shown in Figure 2, when the cathode top angle is small (θ = 40°, as Figure 5 As shown), at an initial field emission current of 2 mA, after nearly 30 hours of testing, the field emission current was about 1.75 mA ( Figure 7 ), showing good field emission lifetime; when the cathode top angle is large (θ=55°, such as Figure 4 As shown), at an initial field emission current of 2 mA, after about 30 hours of testing, the field emission current decreased to 1.5 mA ( Figure 8 ), the cathodes at two different angles all show good field emission performance. The field emission performance of the cathodes at different angles in Example 2 is slightly better than that in Example 1, and the field emission performance of the cathodes at different angles in Examples 3 to 7 is basically at the same level as that in Example 1, indicating that the sandwich-like composite cathode material of the present invention has good field emission current stability and can achieve a good field emission life.

[0078] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A sandwich-like composite cathode material, characterized in that: The composite cathode material comprises a cathode material layer I, a first metal bonding layer and a cathode material layer II which are stacked in sequence; The cathode material layer I and the cathode material layer II are both layers comprising at least one material selected from graphene, carbon nanotubes, carbon cloth and ZnO nanowires; the first metal bonding layer is formed by melting and solidifying metal particles.

2. The composite cathode material according to claim 1, characterized in that: The thickness of the cathode material layer I is 3-7 μm, and the thickness of the cathode material layer II is 3-7 μm.

3. The composite cathode material according to claim 1, characterized in that: The composite cathode material further comprises a second metal bonding layer, wherein the second metal bonding layer comprises a plurality of stacked units, wherein the stacked units comprise a metal layer and a thin film layer stacked in layers; The second metal bonding layer is located between the cathode material layer I and the first metal bonding layer, and / or the second metal bonding layer is located between the cathode material layer II and the first metal bonding layer, and the thin film layer is arranged close to the first metal bonding layer; The thin film layer is a layer comprising at least one material selected from graphene, carbon nanotubes, carbon cloth, ZnO nanowires, Ag nanowires and Cu nanowires; The metal layer is formed by melting and solidifying metal particles.

4. The composite cathode material according to claim 3, characterized in that: The thickness of the thin film layer is 3-7 μm; or, the thin film layer is Ag nanowire or Cu nanowire and is made of a different metal material from the first metal adhesive layer and the metal layer. 5 . The composite cathode material according to claim 1 , wherein the metal particles are any one of Ni particles, Cu particles, Au particles and Ag particles.

6. A method for preparing a sandwich-like composite cathode material, characterized in that: The following steps are involved: Placing the metal particle layer I between the cathode material layer I and the cathode material layer II, heating to melt the metal particles, and cooling to solidify, thereby obtaining a composite cathode material with a sandwich structure; The cathode material layer I and the cathode material layer II are both layers of at least one material selected from graphene, carbon nanotubes, carbon cloth and ZnO nanowires.

7. The preparation method according to claim 6, characterized in that: A plurality of stacked units are further arranged between the metal particle layer I and the cathode material layer I, or between the metal particle layer I and the cathode material layer II. The stacked units include a stacked metal particle layer II and a thin film layer, and the thin film layer is arranged close to the metal particle layer I. The thin film layer is a layer including at least any one material of graphene, carbon nanotube, carbon cloth, ZnO nanowire, Ag nanowire and Cu nanowire.

8. Application of a sandwich-structured composite cathode material in a cold cathode electron source, characterized in that: The composite cathode material is the composite cathode material according to any one of claims 1 to 6, or the composite cathode material prepared by the preparation method according to claim 7 or 8.

9. A field emission cathode, characterized in that: The field emission cathode comprises the composite cathode material according to any one of claims 1 to 5, or the composite cathode material prepared by the preparation method according to claim 6 or 7.

10. The field emission cathode according to claim 9, characterized in that: The field emission cathode has an emission tip, and the angle of the emission tip is 40° to 55°.

Citation Information

Cited By

  • Diamond composite substrate, preparation method of diamond composite substrate and GaN device

    CN120388885A